(untitled) (Purbanchal University Health Journal, 2025)
Introduction: An adverse cutaneous drug reaction is defined as any unwanted alteration in the structure or function of the skin, its appendages, or mucous membranes resulting from drug exposure ranging from transient maculopapular rashes to life-threatening conditions such as toxic epidermal necrolysis. This study was aimed to find the prevalence of cutaneous adverse drug reaction in patients who visited the department of Dermatology at a tertiary care centre. Method: A descriptive cross-sectional study was conducted at Nobel Medical College from January 2021 to February 2023. Participants were enrolled using convenience sampling. A comprehensive clinical history was recorded, encompassing the morphological pattern, progression, and duration of lesions. Adverse drug reactions (ADRs) were classified into four categories—definite, probable, possible, and unlikely based on Naranjo’s causality assessment scale. Point estimates along with 95% confidence intervals were calculated for data analysis. Result: Out of 4802 patients, 73 (1.52%) patients had cutaneous adverse drug reaction (1.18-1.86, 95% Confidence Interval). The most common morphological pattern of cutaneous adverse drug reaction (CADR) in current study was exanthematous (47.9%) followed by Steven- Johnson Syndrome (12.3%), fixed drug eruptions (12.3%) and urticaria (12.3%). The most common morphological pattern of CADR in current study was exanthematous(47.9%) followed by SJS (12.3%), FDE (12.3%) and urticaria (12.3%). As per Naranjo ADR probability scale, 42 cases (57.5%) were certain and 21 cases (28.8%) were probable Conclusion: This study assessed the prevalence of cutaneous adverse drug reaction in tertiary care center of Eastern Nepal. It also established the most common type of morphological patterns of cutaneous drug reaction and the most common groups of drugs involved.